2018
DOI: 10.6033/specialeducation.2.25
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Automatic Semantic Processing in Children With High-Functioning Pervasive Developmental Disorders Having Reading Difficulty

Abstract: Inhibition of automatic semantic processing was examined in children who have high functioning-pervasive developmental disorders (HF-PDD) with or without reading di culty and in typically developing children. In Experiment 1, lexical decision tasks were conducted under three priming conditions: (1) normal character condition, (2) transposed-letter internal nonwords condition, and (3) transposed-letter external nonwords condition.e results indicated that all participants displayed semantic priming under the nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
(11 reference statements)
0
1
0
Order By: Relevance
“… Woods et al (2013) found that AS patients were commonly characterized by having difficulties in social skills and communication, which can present challenges in everyday functioning. Yanai and Maekawa (2014) found that children with AS had more difficulties with automatic semantic processing than children with normal development. Herrington et al (2007) indicated that AS patients showed significantly decreased activity between the right superior temporal gyrus and the angular gyrus compared with the HC.…”
Section: Discussionmentioning
confidence: 94%
“… Woods et al (2013) found that AS patients were commonly characterized by having difficulties in social skills and communication, which can present challenges in everyday functioning. Yanai and Maekawa (2014) found that children with AS had more difficulties with automatic semantic processing than children with normal development. Herrington et al (2007) indicated that AS patients showed significantly decreased activity between the right superior temporal gyrus and the angular gyrus compared with the HC.…”
Section: Discussionmentioning
confidence: 94%